Children's self-efficacy and proxy efficacy for after-school physical activity - Dzewaltowski, David A.; Geller, Karly S.; Rosenkranz, Richard R.; Karteroliotis, Konstantinos (My University, 2011)
Problem: This study evaluated the psychometric properties of a scale measuring children's self-efficacy and proxy efficacy for physical activity at after-school programs and at home. Proxy efficacy was defined as children's confidence in their skills and abilities to get adults to act in their interest to provide physical activity opportunities. Methods: Children (grades 4 through 6) attending after-school programs completed a self-efficacy questionnaire relevant to their physical activity. Factorial validity was assessed with an exploratory factor analysis (n = 107) and a confirmatory factor analysis (n = 187). Next, criterion-related validity was assessed using a mixed-model analysis of covariance with school as a random effect and children level variables as fixed effects. Internal consistency reliability was assessed using Cronbach's alpha. Results: The questionnaire assessed three separate constructs: self-efficacy to be physically active (SEPA), proxy efficacy to influence parents to provide physical activity opportunities (PEPA-P), and proxy efficacy to influence after-school staff to provide physical activity opportunities (PEPA-S). Males had greater SEPA than females. Children who perceived greater physical activity opportunities during after-school time had greater SEPA, PEPA-P, and PEPA-S than children attending schools with fewer physical activity opportunities. Children attending schools with lower concentrations of racial/ethnic diversity and higher socioeconomic status (SES) had greater PEPA-P compared to children attending greater racial/ethnic diversity and low-SES schools. Conclusions: Self-efficacy for physical activity is a multicomponent construct and can be assessed in elementary-aged children using the reliable and valid instrument confirmed in the current study.
Keywords: Physical activity; Proxy efficacy; Self-efficacy; Children; Mediator; After-school; Exercise; Socioeconomic status